Minimal residual disease in EGFR-mutant non-small-cell lung cancer - Bain, Nathan T.; Wang, Yang; Arulananda, Surein (Frontiers in Oncology, 2022)
Targeted therapy with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) is an effective treatment for EGFR-mutant non-small-cell lung cancer (NSCLC), however most patients invariably relapse after a period of minimal residual disease (MRD). This mini-review explores the mechanistic pathways leading to tumour dormancy, cellular senescence and epigenetic changes involving YAP/TEAD activation. We describe the various approaches of utilising TKIs in combination with agents to intensify initial depth of response, enhance apoptosis and target senescence-like dormancy. This mini-review will also highlight the potential novel therapies under development targeting MRD to improve outcomes for patients with EGFR-mutant NSCLC.